Edukasi Pentingnya Laporan Keuangan Sederhana Bagi Pelaku UMKM Laundry dan Penjual Bensin Eceran - Pratiwi, Windityan Yahya; Astuti, Tutut Dewi (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
MSMEs are businesses carried out by individuals, groups, small business entities, or households. Some MSME players have not prepared financial reports due to a lack of education and understanding of financial reports. This community service aims to provide education to Mrs. Pariyem as a laundry business owner and Mr. Martono as a retail petrol sales business owner in Bantul Regency regarding the importance of simple financial reports in managing business finances. Simple financial reports help business people record income, expenses and profits regularly, so they can monitor business performance and improve decision making. The implementation method used is to educate business actors and help create simple financial reports. The result of this activity is that MSME business actors in Bantul district, especially the laundry business Bu Pariyem and the retail petrol seller Pak Martono, can implement or make simple financial reports. The conclusion is that Bu Pariyem's laundry business and Mr. Martono's retail petrol seller can realize the importance of financial reports and can make financial reports for the businesses they own.